(3Yf GdKhQI aj GdKhQI h HGdKhQI (B:s (3MhGQ eY HheOjf (B/s - (3GdNhdj,dWaj s ((3GdLRGFQ (B:s (3GdJLeY GdLRGFQj GdHheOjfj GdESdGej ,s)
(3YfOeG JWdY Ydi gPG GdcJGH SJLO ajg GLGHGJ dYOI fbGW (B1-(3bVjI Sj GdMhGS eY OjZhd (B2- (3GJaGbjGJ GjajGf h ehba HheOjf efgG (B3-(3bVjI GjJ GMeO (B4-(3bVjI GdYbjO TYHGfj (B5-(3bVjI GdejdjTjG GdJj GfTGgG GMeO Hf HdI (B6-(3GSHGH JUMjM (B19 (3LhGf (B1965 7-(3bVjIJhbja MQHj(B8-(3bUI SMH GehGd LHgI GdJMQjQ GdhWfj ef WQa GdeQMhe NjQ NdGd GdSfI (B1963s
Keywords: (3ghGQj HheOjfs